THE APPLICATION OF THE 2013 CURRICULUM IN THE EARLY COGNITIVE ASPECT OF CHILD TARBIYATUL ISLAM NGAGEL DUKUHSETI PATI CENTRAL JAVA - Sumiyati Sumiyati; Afridatul Ulwiyah (UIN Sultan Maulana Hasanuddin Banten, 2023)
The educational curriculum is very important for the implementation and process of education. Without the right curriculum, students will not get the appropriate learning targets. Along with the development of the curriculum era in the world of education, it also continues to experience changes where these changes are adapted to the needs of each student. The research method used is descriptive qualitative. Data was collected using interviews, observation, and documentation techniques on daily learning activities at school. The results showed that: 1) the implementation of 2013 curriculum-based learning at RA Tarbiyatul Islam Ngagel went well. 2) The factors supporting the implementation of learning are class decoration, there are extracurriculars.